Priority sectors for development in Indonesia - Recky H. E. Sendouw (Privietlab, 2025)
This study aims to identify and assess the priority sectors of national development in Indonesia by employing government policies, economic data, and strategic planning papers from 2020–2025. Data were collected using a qualitative descriptive methodology from national development plans, ministerial reports, and peer-reviewed journal papers. The findings indicate that Indonesia's current development agenda focuses on human capital enhancement, infrastructure, digital transformation, food and energy sovereignty, and green economy initiatives. These areas demonstrate the government's dedication to inclusive and sustainable growth, aligning with national objectives and global commitments, such as the Sustainable Development Goals (SDGs). This research underscores the importance of intersectoral collaboration, fiscal prudence, and innovation in enabling effective execution. Policy recommendations include enhancing the capacity of local governments, improving public-private partnerships, and refining data-driven monitoring systems. This study contributes to the scholarly discourse on development administration by situating Indonesia's national priorities within its own social, political, and economic framework.